Who is the Celebrity Endorser? A Content Analysis of Celebrity Endorsements. Issue 4 (8th August 2018) - Schimmelpfennig, Christian
ABSTRACT: Much of the academic literature suggests that 25%–30% of all advertising in western countries uses celebrities. The celebrity endorser is considered a famous personality who is recognized by name and face by the general public. This study investigates the usage of different types of celebrities in German print advertising. It finds that the share of celebrity endorsements as defined by the literature, adverts that feature individuals known to the general public, is as low as 2.9%. Moreover, the study's results are compared with results from US studies and it is shown in what product categories celebrity usage differs substantially between markets. Conclusions are drawn as to where advertisers need to adapt their ad strategy to differentiate their brand's advertising from the competition in the German and the US market.